Development of gene polymorphisms in meditators of nonalcoholic fatty liver disease - Wang, Chun (Biomed Rep, 2017)
Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide, the morbidity of which closely correlates with diversity of ethnicity, minority, family and location. Its histology spans from simple steatosis, to nonalcoholic steatohepatitis, which ultimately results in fibrosis, cirrhosis and hepatocellular carcinoma. The accelerating prevalence of NAFLD is due to an incremental incidence of metabolic syndrome that is distinguished by dyslipidemia, glucose impairment, obesity, excessive oxidative stress and adipocytokine impairment. Additionally, the pathogenesis of NAFLD is thought to be a multifactorial and complicated disease associated with lifestyle habits, nutritional factors and genetics. However, the pathogenesis and underlying mechanism in the development of NAFLD caused by genetics remains unclear. People have been increasingly emphasizing on the relationship between NAFLD and gene polymorphisms in recent years, with the aim of having a comprehensive elucidation of associated gene polymorphisms influencing the pathogenesis of the disease. In the current article, the authors attempted to critically summarize the most recently identified gene polymorphisms from the facets of glucose metabolism, fatty acid metabolism, oxidative stress and related cytokines in NAFLD that contribute to promoting the progression of the disease.